1994
DOI: 10.1021/jm00027a024
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzyme-specific glutathione-S-transferase inhibitors: design and synthesis

Abstract: Glutathione-S-transferase (GST) isozyme-selective inhibitors were designed by an empirically guided strategy. In the first phase, literature data were used to select C-terminal modifications which generated maximum variation in the catalytic efficiency (Vmax/Km) for glutathione (GSH) analogs used as substrates with different rat GSTs. Also, on the basis of literature data, the sulfhydryl group was functionalized with a selection of alkyl and aryl groups to maximize potential isozyme specificity. Affinity chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Literature search on previous works has also shown that glutathione conjugates are involved in inhibition of GST [53,54]. One recent study revealed that GSH conjugate of doxorubicin inhibited GST activity [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature search on previous works has also shown that glutathione conjugates are involved in inhibition of GST [53,54]. One recent study revealed that GSH conjugate of doxorubicin inhibited GST activity [53].…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin showed an increased cytotoxicity not only towards MDR cells but also doxorubicin sensitive cells suggesting that glutathione conjugates of drugs such as doxorubicin may play a vital role in the GST expression and hence drug induced cytotoxicity. Lyttle group also reported that a number of compounds which are coupled to the thiol group of glutathione showed significant inhibition of GST activity [54]. Tyrosinase catalyzes the metabolism of quercetin to quinone and glutathione adducts [55].…”
Section: Discussionmentioning
confidence: 99%
“…The reason the alpha class and not the others react with GSB is still not clear. The differences could potentially be due to binding preferences, but similar compounds have been shown to bind to the alpha, mu, and pi class with K D values that are comparable (37). Also, within the alpha class, the enzymes display different substrate preferences (29,38,39), and the crystal structures (6,40) also reveal differences; for example, the H-site of hGST A4-4 appears to be more narrow and elongated than that of hGST A1-1.…”
Section: Discussionmentioning
confidence: 99%
“…Almost two decades ago, clinical studies indicated ethacrynic acid as a candidate for modulation of drug resistance (Lacreta et al, 1994). At the same time, the selective GST-π inhibitor TER-117 was synthesized (Lyttle et al, 1994 include on references), but there are no recent studies with this. Other GST-π specific inhibitors were able to revert multiple drug resistance in cholangiocarcinoma (Nakajima et al, 2003).…”
Section: Introductionmentioning
confidence: 99%